Pengaruh Keadilan terhadap Kepuasan dan Kepatuhan Wajib Pajak - Albari Albari (Universitas Islam Indonesia, 2008)
In general, tax payment has been perceived merely as a citizen’s obligation which has tobe performed, paying less attention to the interests of Tax Payers. Therefore, this studyproposes to reveal possibilities of Tax Payers’ compliance because of just services givenby Tax Office and of Tax Payers’ satisfaction upon the justice itself. In this research,concept of justice is classified into distributive, procedural and interactional justices. Thisresearch involves 166 respondents, gained through convenience sampling from Tax Payersin KPP II. Using path analysis, this research results in the fact that justice affects,directly or indirectly, the compliance through intervening variable of satisfaction. Whilstbased on regression analysis, it has been shown that distributive justice and the satisfactionof Tax Payers upon procedural justice positively affect the Tax Payers’ compliance.Keywords: justice, satisfaction, compliance.